Over the counter hearing aids self-fitting using the Gaussian Process Classification - Boven, Christopher; Turek, Joseph; Dunckley, Kathleen; Richter, Claus-Peter (Frontiers in Audiology and Otology, 2024)
To provide better access to hearing aids and lower the devices' costs for patients with mild to moderate hearing loss, the Food and Drug Administration (FDA) changed its rules for hearing aid distribution, making them available to consumers over-the-counter without the supervision, involvement, or prescription of a licensed health care professional. While this regulation provides some patients direct access to hearing aids, the hearing aid fitting creates challenges for the patients and the hearing aid providers. OTC hearing aids should be programmable outside of a clinical setting. This study demonstrates that the self-fitting of hearing aids does not differ significantly from and is non-inferior to the fitting of the device by a licensed audiologist. Hearing aid and patient performance after fitting the device by the patient (self-fitting) and a certified audiologist (clinical fitting) were compared in a laboratory setting and a field trial. The laboratory session used a repeated-measures design to assess the reliability and validity of the self-fitting method. A 7-14 days of wear time was used for the field study. The outcome measures for the laboratory session were the differences in acoustical real-ear aided response (REAR). For the wear-time trial, the outcome was the clinical self-report measure of benefit (Abbreviated Profile of Hearing Aid Benefit, APHAB). The benefit of the hearing aid was tested after the self-fitting and the clinical fitting of the hearing aid with a speech-in-noise test (QucikSIN). The test outcomes showed no statistically significant differences between repeated self-fitting and clinical fitting of the hearing aids. The hearing aid selffitting was non-inferior to the clinical fitting.